Self-folding hydrogel bilayer for enhanced drug loading, encapsulation, and transport - Huang, Hen Wei; Petruska, Andrew J.; Sakar, Mahmut Selman; Skoura, Maria; Ullrich, Franziska; Zhangm, Qi; Pane, Salvador; Nelson, Bradley J. (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2016)
Hydrogel-based robotic microdevices are currently investigated for minimally invasive medical procedures. Hydrogels are especially suited to targeted drug delivery applications as they are able to carry several times more drug solution than its dry weight. A major drawback of these system is that drug release takes place before reaching the targeted area in the body. We introduce a strategy based on a self-folding bilayer to prevent release during transportation without hindering the drug loading efficiency of the hydrogel. The drug is loaded into the hydrogel matrix at room temperature. When the temperature is increased to body temperature, the hydrogel-matrix collapses and the self-folded bilayer refolds into another tube. In this configuration, we observed a significant reduction in drug leakage with less than 5% drug loss during encapsulation. Finally, we demonstrate that the tube can be manipulated magnetically, which shows its potential use in targeted drug delivery applications.
CRIS-Team Scopus Importer:2023-03-21